Feasibility of Using Natural Rubber (NR) Latex Foam as a Soft Robotic Finger: Role of Foaming Agent in Morphology and Dynamic Properties of NR Latex Foam - Chuayprakong, Sunanta; Chuchat, Jiraphat; Poruksa, Thorranin; Soccio, Michelina (Applied Science and Engineering Progress, 2021)
Sarcopenia caused by ageing and muscle loss is mostly found in the elderly people. Since a number of older people have been increased, a device which assists with grasping can play an important role in an ageing society. The purpose of this research is to select the material which is potentially a part of soft robotic actuator. Natural rubber (NR) latex produced locally in Thailand is intentionally chosen and chemically vulcanized by using a conventional vulcanization system into a molded fingered foam. The research focuses on varying the amount of foaming agent (Benzene sulfonyl hydrazide, BSH). Effect of foaming agent quantity on morphology and dynamic properties of the prepared natural rubber foam was elucidated. The suitable foam formula is selected and molded as the human fingers in the structure of a potential soft robotic actuator which were tested for the movement.